Mutational profile of ZBTB16‐RARA‐positive acute myeloid leukemia. (27th May 2021) - Fabiani, Emiliano; Cicconi, Laura; Nardozza, Anna Maria; Cristiano, Antonio; Rossi, Marianna; Ottone, Tiziana; Falconi, Giulia; Divona, Mariadomenica; Testi, Anna Maria; Annibali, Ombretta; Castelli, Roberto; Lazarevic, Vladimir; et al.
Abstract: Background: The ZBTB16‐RARA fusion gene, resulting from the reciprocal translocation between ZBTB16 on chromosome 11 and RARA genes on chromosome 17 [t(11;17)(q23;q21)], is rarely observed in acute myeloid leukemia (AML), and accounts for about 1% of retinoic acid receptor‐α ( RARA) rearrangements. AML with this rare translocation shows unusual bone marrow (BM) morphology, with intermediate aspects between acute promyelocytic leukemia (APL) and AML with maturation. Patients may have a high incidence of disseminated intravascular coagulation at diagnosis, are poorly responsive to all‐ trans retinoic acid (ATRA) and arsenic tryoxyde, and are reported to have an overall poor prognosis. Aims: The mutational profile of ZBTB16‐RARA rearranged AML has not been described so far. Materials and methods: We performed targeted next‐generation sequencing of 24 myeloid genes in BM diagnostic samples from seven ZBTB16‐RARA + AML, 103 non‐RARA rearranged AML, and 46 APL. The seven ZBTB16‐RARA ‐positive patients were then screened for additional mutations using whole exome sequencing ( n = 3) or an extended cancer panel including 409 genes ( n = 4). Results: ZBTB16‐RARA +AML showed an intermediate number of mutations per patient and involvement of different genes, as compared to APL and other AMLs. In particular, we found a high incidence of ARID1A mutations in ZBTB16‐RARA +AML (five of seven cases, 71%). Mutations in ARID2 and SMARCA4, other tumor suppressor genes also belonging to SWI/SNF chromatin remodeling complexes, were also identified in one case (14%). Discussion and conclusion: Our data suggest the association of mutations of the ARID1A gene and of the other members of the SWI/SNF chromatin remodeling complexes with ZBTB16‐RARA +AMLs, where they may support the peculiar disease phenotype. Abstract : This is the first report showing the mutational landscape of the rare ZBTB16‐RARA rearranged acute myeloid leukemia (AML). We identified a high frequency of ARID1A mutations, suggesting the involvement of the SWI/SNF chromatin remodeling complexes in the clinical presentation, acute promyelocytic leukemia‐like morphology and all‐ trans retinoic acid/arsenic trioxide treatment resistance of ZBTB16‐RARA rearranged AMLs.